Photocatalytic purification of dye-containing wastewater using a novel embedded hybrid TiO2–slag catalyst heterojunction nanocomposite coupled with statistical models: A sustainable and techno-economic approach - Kingsley Safo; Norbert Onen Rubangakene; Hussien Noby; Ahmed H. El-Shazly (Water Science and Engineering)
The steel industry produces many byproducts, requiring extensive land for storage and causing significant environmental contamination. Industrial effluents discharged into water bodies negatively impact both aquatic ecosystems and human health. To solve this problem, this study synthesized a composite of titanium dioxide (TiO2) and steel slag nanocomposites (SSNC) at a 1:2 mass ratio to create a robust photocatalyst for the treatment of synthetic wastewater. The efficacy of this catalyst in degrading various dye pollutants, including methylene blue (MB), was tested under simulated solar light conditions. Comprehensive analyses were conducted to assess the physical and chemical characteristics, crystalline structure, energy gap, and point of zero charge of the composite. The TiO2-SSNC composite catalyst exhibited excellent stability, with a point of zero charge at 8.342 and an energy gap of 2.4 eV. The degradation process conformed to pseudo-first-order kinetics. Optimization of operational parameters was achieved through the response surface methodology. Reusability tests demonstrated that the TiO2-SSNC composite catalyst effectively degraded up to 93.41% of MB in the suspended mode and 92.03% in the coated mode after five cycles. Additionally, the degradation efficiencies for various dyes were significant, highlighting the potential of the composite for broad applications in industrial wastewater treatment. This study also explored the degradation mechanisms and identified byproducts, establishing a pathway for contaminant breakdown. The cost-benefit analysis revealed a total cost of 0.842 8 USD per cubic meter for each treatment activity, indicating low operational and production costs. These findings underscore the promise of the TiO2-SSNC composite as a cost-effective and efficient alternative for wastewater purification.